ANALISIS SISTEM INFORMASI PEMASARAN BERBASIS WEB PADA TOKO BILLY - Nst, Nanda Saputra; Sari, Indah Nilam; Okatviyanti, Senja Gadis (Jurnal Ilmiah Sistem Informasi, 2024)
Currently, the marketing at the Billy Shop is done manually, namely through phone calls, sms and coming directly to the customer's home to offer the products/goods offered, so that it can save time (24-hour marketing) and reduce costs so that it can increase the revenue turnover of the Billy Shop. The purpose of this research is to analyze and design a web-based marketing information system at Billy Shop to improve marketing. The method used in this study is the prototype method according to the title taken, namely the analysis and design of the marketing information system in Billy's store. The web-based / Online marketing system is one of the marketing service facilities that must be used continuously by the store in order to achieve good product marketing, according to the advancement of information technology, where users can find out marketing information directly about the products marketed by the store. For the next researcher, it is recommended to increase the number of links, images of marketing products to attract visitors and use advertising marketing services